Transnational literature : the basics - Jay, Paul, 1946- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Transnational Literature: The Basics provides an indispensable overview of this important new field of study and the literature it explores. It concisely describes the various ways in which literature can be understood as being "transnational", explains why scholars in literary studies have become so interested in the topic, and discusses the economic, political, social, and cultural forces that have shaped its development. The book explores a range of contemporary critical approaches to the subject, highlighting how subjects like globalisation, cosmopolitanism, diaspora, history, identity, migration, and decolonization are treated by both scholars in the field and the writers they study. The literary works discussed range across the globe and include fiction, poetry, and drama by writers including Jhumpa Lahiri, Chimamanda Ngozi Adichie, Jenny Erpenbeck, Aleksandar Hemon, Viet Thanh Nguyen, Derek Walcott, Louise Bennett, Xiaolu Guo, Sally Wen Mao, Wole Soyinka, and many more. This survey stresses the range and breadth - but also the intersecting interests - of transnational writing, engaging the variety of subjects it covers and emphasizing the range of literary devices (linguistic, formal, narrative, poetic, and dramatic) it employs. Highlighting the subjects and issues that have become central to fiction in the age of globalization, Transnational Literature: The Basics is an essential read for anyone approaching study of this vibrant area"--
Conceptualizing transnational literature. The nation and beyond -- Transnationalizing literary studies -- What is transnational literature? -- Reading transnational literature. The lay of the land -- Mobility -- Borders -- Migration -- Identity -- History -- Transnational theatre.
OCLC-licensed vendor bibliographic record.
Keywords: Literature and transnationalism; LANGUAGE ARTS & DISCIPLINES / Literacy; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; LITERARY COLLECTIONS / General